1983
DOI: 10.1063/1.332074
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on electrical properties of thermal neutron transmutation doped Ge

Abstract: A neutron transmutation doping technique was applied to the high purity n-type germanium with 50 Ω cm (n=5.9×1013/cm3). For a neutron flux density of 5×1011/cm2 s and an irradiation time of 60 min, the doped Ge was converted into p type with 7 Ω cm ( p=3.5×1014/cm3). By neutron irradiation it has been possible to introduce the shallow acceptors resulting from the damage in addition to gallium atoms as acceptors. The recovery of radiation damage was evaluated by the improvements of some electrical properties fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…S 0 optical transitions in GeO color centers [21]. With increase Table 2 The impurity concentration of codoped Ge-ncs sample Neutron fluence (neutrons/cm 2 ) N Ga /N 0 N As /N 0 2.2 · 10 18 1.35 · 10 À6 4.02 · 10 À7 1.9 · 10 19 1.17 · 10 À5 3.47 · 10 À6 of annealing temperature, the energy of PL peak at 620 nm shifts to low-energy side, which is consistent with quantum confine effect. So the PL peak at 620 nm is related to exciton recombination luminescence [22][23][24].…”
Section: Photoluminescence Of Ge-ncsmentioning
confidence: 99%
See 2 more Smart Citations
“…S 0 optical transitions in GeO color centers [21]. With increase Table 2 The impurity concentration of codoped Ge-ncs sample Neutron fluence (neutrons/cm 2 ) N Ga /N 0 N As /N 0 2.2 · 10 18 1.35 · 10 À6 4.02 · 10 À7 1.9 · 10 19 1.17 · 10 À5 3.47 · 10 À6 of annealing temperature, the energy of PL peak at 620 nm shifts to low-energy side, which is consistent with quantum confine effect. So the PL peak at 620 nm is related to exciton recombination luminescence [22][23][24].…”
Section: Photoluminescence Of Ge-ncsmentioning
confidence: 99%
“…The production rate of 75 As is 0.5 · 10 À2 atoms/cm 3 / neutrons/cm 2 . The isotope 77 Se is produced from reaction (6), but this isotope is the deep donor impurity which has level of 0.14 and 0.28 eV in the forbidden band and is not effective as the donor impurity [19]. Therefore, the net acceptor and donor concentration can be calculated by formula N impurity = N 0 k i d i ut, where N 0 is concentration of Ge atoms in the lattice (cm -3 ), k i is the abundance of isotope, u is the intensity of the thermal neutron flux (neutrons/cm 2 AE s), t is the exposure time (s), d i is the production rate of Ga and As.…”
Section: Ntdmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several attempts have been made recently to improve the uniformity of QD distribution. Neutron transmutation doping ͑NTD͒ is a technique which utilizes the nuclear reaction of thermal neutrons with the isotopes in a semiconductor material, [15][16][17] and it has been reported that impurities are distributed homogeneously in a material [18][19][20][21][22] by using NTD. Achieving uniform QDs under the 3D confinement conditions remains one of the most daunting challenges ͑in quantum-dot formation, etc͒.…”
Section: Fabrication Of Uniform Ge-nanocrystals Embedded In Amorphousmentioning
confidence: 99%
“…The NTD method is used as a means of homogeneously introducing impurity atoms into semiconducting materials such as Si, a-Si:H [2], Ge [3], GaAs [4,5], GaP [6,7], InSe [8], GaS [9], GaN [10] and so on. Especially, NTD-Si has already been commercialized as a material for high power devices.…”
mentioning
confidence: 99%